Lupus nephritis: The regulatory interplay between epigenetic and MicroRNAs - Xu, Ning; Liu, Jie; Li, Xiangling (Frontiers in Physiology, 2022)
MicroRNAs (miRNAs) are endogenous, small, non-coding RNA molecules that act as epigenetic modifiers to regulate the protein levels of target messenger RNAs without altering their genetic sequences. The highly complex role of miRNAs in the epigenetics of lupus nephritis (LN) is increasingly being recognized. DNA methylation and histone modifications are focal points of epigenetic research. miRNAs play a critical role in renal development and physiology, and dysregulation may result in abnormal renal cell proliferation, inflammation, and fibrosis of the kidneys in LN. However, epigenetic and miRNA-mediated regulation are not mutually exclusive. Further research has established a link between miRNA expression and epigenetic regulation in various disorders, including LN. This review summarizes the most recent evidence regarding the interaction between miRNAs and epigenetics in LN and highlights potential therapeutic and diagnostic targets.